Afrofuturist Vision And Identity: Perspectives On Binti And Dawn (Journal of Namibian Studies : History Politics Culture, 2023)
Afrofuturism, a genre that merges science fiction, fantasy, and African diaspora culture, serves as a powerful framework for exploring Black identity, technology, and history. This paper examines Nnedi Okorafor’s Binti and Octavia Butler’s Dawn as exemplars of Afrofuturist narratives that reimagine identity through the lens of cultural hybridity, transhumanism, and futuristic possibilities. Binti, a Himba girl traveling to an intergalactic university, maintains her cultural heritage while navigating alien encounters. Conversely, Lilith Iyapo in Dawn undergoes genetic modification and negotiates her human identity in a post-apocalyptic world ruled by extraterrestrials. Both protagonists resist marginalization and forge new understandings of self and community through the intersection of race, technology, and resilience. This study highlights Afrofuturism’s role in challenging dominant narratives, reclaiming Black histories, and envisioning alternative futures rooted in empowerment and collective liberation.